Scenario Insight of Energy Transition: A Lesson Learned from European Union to Indonesia - Ariana Soemanto; Raldi Hendro T. Koestoer (Indonesian Journal of Energy, 2023)
Almost all countries committed to tackling climate change as agreed in the Paris Agreement in 2015. In developed countries, the European Union (EU) issued the European Green Deal (EGD) with a target of 55% emissions reductions by 2030 and net zero emissions by 2050. Among developing countries, Indonesia has similar targets, which are 29% to 41% emission reductions by 2030 and net zero emissions by 2060 or sooner. EU countries and Indonesia also aim to implement energy transitions by increasing renewable energy shares, especially in the electricity sector, to reduce their emissions. Nevertheless, the EU countries have state-of-art research related to technologies and clean energy policies, allowing the EU as the first continent to commit to net-zero emissions by 2050. Our study aims to take lessons from recommendations in EGD and analyze their fitness for implementation in Indonesia. The research was conducted through a qualitative approach using secondary information and relevant references. We found that almost all recommendations for the energy transition in the EU electricity sector are relevant to Indonesia, except nuclear power plants and electricity tariff policies.